2016
DOI: 10.1016/j.clinph.2015.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-invasive brain stimulation on post-stroke dysphagia: A systematic review and meta-analysis of randomized controlled trials

Abstract: Objective The primary aim of this review is to evaluate the effects of non-invasive brain stimulation on post-stroke dysphagia. Methods Thirteen databases were systematically searched through July 2014. Studies had to meet pre-specified inclusion and exclusion criteria. Each study's methodological quality was examined. Effect sizes were calculated from extracted data and combined for an overall summary statistic. Results Eight randomized controlled trials were included. These trials revealed a significant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 89 publications
6
113
0
3
Order By: Relevance
“…Moreover, depending on the site of stimulation, recent systematic reviews and metaanalyses reported different results regarding the effect of NIBS. For instance, Yang et al [12] reported no significant difference according to stimulation sites; by contrast, Pisegna et al [13] found a significantly better effect size resulting from the contralesional stimulation as compared to the ipsilesional stimulation. The latter review even included one study that applied a combined method for 5 Hz rTMS over the contralesional hemisphere with the pharyngeal electrical stimulation [14].…”
Section: Article In Pressmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, depending on the site of stimulation, recent systematic reviews and metaanalyses reported different results regarding the effect of NIBS. For instance, Yang et al [12] reported no significant difference according to stimulation sites; by contrast, Pisegna et al [13] found a significantly better effect size resulting from the contralesional stimulation as compared to the ipsilesional stimulation. The latter review even included one study that applied a combined method for 5 Hz rTMS over the contralesional hemisphere with the pharyngeal electrical stimulation [14].…”
Section: Article In Pressmentioning
confidence: 97%
“…Moreover, depending on the stimulating site, previous systematic reviews reported different results regarding the effect of non-invasive brain stimulation (NIBS). Specifically, one review reported no significant difference according to the stimulation site [12], while another review found a significantly better effect size resulting from the contralesional stimulation as compared to the ipsilesional stimulation [13]. The latter review included a combined brain and peripheral stimulation study, which applied 5 Hz rTMS over the contralesional hemisphere in combination with the pharyngeal electrical stimulation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Information on neural control, both in terms of direct measurement of neural function and indirectly through lesion studies, has become more possible in human subjects through recent innovative techniques such as TMS [3335, 39]. However, understanding specific aspects of neural control is still the realm of implanted electrodes, neural stimulation, and lesions, none of which are possible in human subjects.…”
Section: Animal Research and The Generation Of Performancementioning
confidence: 99%
“…Currently, the focus of treatment studies is shifting from conventional exercise-based swallow therapy towards approaches that modulate the underlying neuronal systems. Neurostimulation devices such as repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS) [5], but also pharyngeal electrical stimulation (PES) [6] have shown promising therapeutic potential to aid dysphagia rehabilitation. However, the underlying neurophysiological modes of action are still only poorly understood because neurophysiological and functional imaging studies are difficult to conduct in severely ill neurologic patients and are therefore mostly restricted to healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%